Դերանվան ուսուցման հիմնախնդիրները գրական արևելահայերենում - Ավետիսյան, Յու. Ս.
Изучение местоимений всегда было предметом дискуссий и дебатов. А это, в свою очередь, создавало трудности в преподавании этих слов. Традиционные подходы к внутренней классификации частей речи, методология, принятая в преподавании местоимений, нуждаются в пересмотре. Основываясь на богатом опыте изучения и описания местоимений в западноармянском языко- знании, в данной статье представлена возможная модификация местоимения и классификация его типов с учетом педагогического подхода. Общий вывод заключается в том, что грамматическое и структурное описание местоимений должно быть представлено в соответствии с признаками, характеризующими части относительного слова. The study of pronouns has always been expressions for discussion and debate. And this, in turn, has created difficulties in teaching those words. The traditional approaches to the internal classification of parts of speech, the methodology adopted in the teaching of pronouns, need to be revised. Based on the rich experience of the study and description of pronouns in Western Armenian linguistics, this article presents a possible modification of pronouns and classification of its types with a pedagogical approach. The general conclusion is that the grammatical and structural description of pronouns should be presented according to the features that characterize the parts of the relative word.
Keywords: Լեզվաբանություն